A nationally representative sample of veteran and matched non-veteran college students: Mental health symptoms, suicidal ideation, and mental health treatment. Issue 2 (8th March 2022) - Valenstein, Marcia; Clive, Rebecca; Ganoczy, Dara; Garlick, James; Walters, Heather M.; West, Brady T.; Kim, Hyungjin M.; Eisenberg, Daniel; Bohnert, Kipling M.; DesJardins, Stephen L.; Zivin, Kara; Lepkowski, James; et al.
Abstract: Objective To assess mental health symptoms, suicidal ideation/behaviors, and treatment among a nationally representative probability sample of student veterans. Participants : Student veterans enrolled in post-secondary educational institutions and matched comparison students. Methods: Sampled participants completed an online survey (n = 1, 838). Analyses accounted for the complex sample design and non-response. Results : Substantial percentages of student veterans screened positive for: depression (36.9%, 95% CI: 31.1-42.7), PTSD (35.7%, 95% CI 29.9-41.5), anxiety (29.5%, 95% CI 26.8-32.2), and suicidal ideation (14.6%, 95% CI 12.1-17.1), with student veterans having odds ratios between 1.7 to 2.4 for positive screens compared to non-veteran students. Only 41.5% (95% CI 33.0-50.0) of student veterans with positive screens received treatment, although they had 50% higher odds of receiving treatment than non-veteran students. Conclusions: Student veterans have high rates of mental health symptoms and low rates of treatment. However, they are more likely to receive treatment than comparison students.